Dendritic Polyurea Polymers. Issue 2 (4th December 2014) - Tuerp, David; Bruchmann, Bernd; Frey, H.; Mecking, S.
<x xml:space="preserve">Abstract</x> Dendritic polymers, subsuming dendrimers as well as hyperbranched or highly branched polymers are well established in the field of polymer chemistry. This review article focuses on urea based dendritic polymers and summarizes their synthetic routes through both isocyanate and isocyanate‐free processes. Furthermore, this article highlights applications where dendritic polyureas show their specific chemical and physical potential. For these purposes scientific publications as well as patent literature are investigated to generate a comprehensive overview on this topic. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>